2018
DOI: 10.22616/erdev2018.17.n158
|View full text |Cite
|
Sign up to set email alerts
|

Influence of rotary grain crusher parameters on quality of finished product

Abstract: At present, modern hammer crushers are widely used for grinding grain, the technological process of which involves suction of the starting material, crushing and pumping the finished product into an intermediate container to separate feed streams. One of the basic working tools is a separating sieve, by means of which the material to be crushed obtains the required dimensions. The aim of the work was experimental finding of a relationship between the parameters of the separating sieve of the crusher and the qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…The studies performed at OAO Put Ilicha farm, Udmurtia, revealed deterioration of quality of crushed grain as a function of screen wear of DKR-5M crusher [5]. Herewith, the screen holes are elongated due to intensive abrasive wear, mainly in the middle portion, and the surface area of holes increases (Fig.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The studies performed at OAO Put Ilicha farm, Udmurtia, revealed deterioration of quality of crushed grain as a function of screen wear of DKR-5M crusher [5]. Herewith, the screen holes are elongated due to intensive abrasive wear, mainly in the middle portion, and the surface area of holes increases (Fig.…”
Section: Resultsmentioning
confidence: 95%
“…Grain for farm livestock is crushed mainly by closed-circuit units with suction of initial material and discharging of final product. In comparison with open-circuit crushers, these units are characterized by lower compliance with the requirements of standards and zootechnology in terms of quality indicators [1][2][3][4][5]. Screen installed in crushing chamber (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…In the world, at least 95 % of all feed grains are crushed by various hammer crushers, which differ in their technological, kinematic, and structural parameters [11][12][13]. Hammer crushers have a significant drawback -the high specific energy consumption.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%